A phylogenetic perspective on the evolutionary processes of floristic assemblages within a biodiversity hotspot in eastern Asia. Issue 4 (27th September 2019) - Li, Rong; Yue, Juan
Abstract : Abstract How to maximize the conservation of biodiversity is critical for conservation planning, particularly given rapid habitat loss and global climatic change. The importance of preserving phylogenetic diversity has gained recognition due to its ability to identify some influences of evolutionary history on contemporary patterns of species assemblages that traditional taxonomic richness measures cannot identify. In this study, we evaluate the relationship between taxonomic richness and phylogenetic diversity of angiosperms at genus and species levels and explore the spatial pattern of the residuals of this relationship. We then incorporate data on historical biogeography to understand the process that shaped contemporary floristic assemblages in a global biodiversity hotspot, Yunnan Province, located in southwestern China. We identified a strong correlation between phylogenetic diversity residuals and the biogeographic affinity of the lineages in the extant Yunnan angiosperm flora. Phylogenetic diversity is well correlated with taxonomic richness at both genus and species levels between floras in Yunnan, where two diversity centers of phylogenetic diversity were identified (the northwestern center and the southern center). The northwestern center, with lower phylogenetic diversity than expected based on taxonomic richness, is rich in temperate‐affinity lineages and signifies an area of rapid speciation. The southern center, with higher phylogenetic diversity than predicted by taxonomic richness, contains a higher proportion of lineages with tropical affinity and seems to have experienced high immigration rates. Our results highlight that maximizing phylogenetic diversity with historical interpretation can provide valuable insights into the floristic assemblage of a region and better‐informed decisions can be made to ensure different stages of a region's evolutionary history are preserved.